A strategic plan for Mahugani Security and Investigation Agency (MSIA) - De Ramos, Rocky M. (School of Management, University of the Philippines Mindanao, 2007)
The Mahugani Security and Investigation Agency (MSIA) is a family corporation owned by the Ramirez family. For the past 5 years, the company has experienced unprecedented growth in its profitability due to the recent addition of armoured car services. MSIA is able to react with the changes in its external environment and it is internally strong considering the location of its agencies outside of Davao City. But with the ever increasing number of competitors and changes in technology, MSIA will always face threats. The strategic plan for MSIA used the framework of David (2001) which focused on the analysis of both external and internal environment so as to come up with strategies and feedback system. In this way, the writer was able to identify the strengths and weakness internally and opportunities and threats for the external environment. Data gathered were from the company manager and stakeholders, company documents, government offices and other secondary sources. The analysis shows the internal strengths such as increasing net income, high profit margins for armoured car services, contract based payment and centralized decision making. In contrast, the internal weaknesses are low profit margin for security services, poor internally sourced funds and equity monitoring and liquidity ratios below standard. The opportunities are increasing demand for security, advancement in technology and expansion of another security agency to other cities. On the other hand, the threats are government intervention on maximum number of employees, competition and application of non personnel security. It is important for MSIA to have strategic goals in order to keep pace with its environment. Thus, for the next five years, the suggested long term objectives for are 1. The agency must strive to position itself to be best security and armoured car service provider in terms of efficiency and profitability by providing customer oriented products and services; 2. To select the clients with emphasis on the high-end market; 3. The agency will combine its traditional core activities with the use of high technology in its operation to increase efficiency and profitability; 4. On top of it is repositioning its network branch expansion to select customers on the high end market, the agency must also undergo a change in mindset by renewing its focus on profitability, efficiency, product and service innovation; 5. To make a dramatic improvement on our human resource management system to be at par with the best run companies since knowing too well that the key element in the pursuit of the organization's goals are the workers. A five year plan was presented with the intention of upgrading human resources, boosting financial performance, being more competitive and offer more product lines. A control system is also provided for timely evaluation. The key result areas as well as the performance indicators are also given to guide the implementation of strategies towards the achievement of their long term goals.